A critical review on the environmental applications of carbon dots. (February 2023) - Hebbar, Akshatha; Selvaraj, Raja; Vinayagam, Ramesh; Varadavenkatesan, Thivaharan; Kumar, Ponnusamy Senthil; Duc, Pham Anh; Rangasamy, Gayathri
Abstract: The discovery of zero-dimensional carbonaceous nanostructures called carbon dots (CDs) and their unique properties associated with fluorescence, quantum confinement and size effects have intrigued researchers. There has been a substantial increase in the amount of research conducted on the lines of synthesis, characterization, modification, and enhancement of properties by doping or design of composite materials, and a diversification of their applications in sensing, catalysis, optoelectronics, photovoltaics, and imaging, among many others. CDs fulfill the need for inexpensive, simple, and continuous environmental monitoring, detection, and remediation of various contaminants such as metals, dyes, pesticides, antibiotics, and other chemicals. The principles of green chemistry have also prompted researchers to rethink novel modes of nanoparticle synthesis by incorporating naturally available carbon precursors or developing micro reactor-based techniques. Photocatalysis using CDs has introduced the possibility of utilizing light to accelerate redox chemical transformations. This comprehensive review aims to provide the reader with a broader perspective of carbon dots by encapsulating the concepts of synthesis, characterization, applications in contaminant detection and photocatalysis, demerits and research gaps, and potential areas of improvement. Graphical abstract: Image 1 Highlights: Various synthesis methods of CDs are briefed. Detection of heavy metals and emerging pollutants are discussed. Various environmental applications of CDs are comprehensively reviewed. Challenges and future prospects of CDs are presented.